Exploring the success factors of hybrid micro-enterprises - Bicho, M.; Nikolaeva, R.; Lages, C.; Ferreira, F. A. F. (Marketing transformation: Marketing practice in an ever changing world: Proceedings of the 2017 Academy of Marketing Science (AMS) World Marketing Congress (WMC), 2017)
This research explores hybrid micro-entrepreneurs’ founding motivations and the transformation of those motivations into visions of success, by applying multiple criteria decision analysis (MCDA). We find that entrepreneurs of hybrid micro-enterprises are driven mostly by noneconomic goals and that those influence their vision of success. The success framework consists of seven indicators (training, professional development, marketing, management, external factors, infrastructures, and organizational aspects). Human capital is perceived as the most important for success – translating the professional motivations for founding. Reversely, external factors, which are usually considered crucial to attain legitimacy, are perceived the least important factors. Given the findings, are hybrid micro-entrepreneurs ready to succeed?